The Influence of Leadership Style on Employee Performance at the Financial and Development Supervisory Agency - Fauzobihi, Fauzobihi; Maringan, Maringan; Supriyadi, Supriyadi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to find out whether leadership style contributes to employee performance. The research population is employees at BPKP East Jakarta. The sample of 48 respondents were employees at the East Jakarta Financial and Development Supervisory Agency (BPKP). Linear regression results for leadership style (X) of 0.477 indicate that for every 1% increase in leadership style value. The correlation between the leadership style variables has a positive influence while the r value is 0.528 (located in the correlation coefficient interval of 0.40-0.55). The correlation between Employee Performance Variables is not very good. This is indicated by the average value of the total employee performance score (Y) of 32.31, located in the class interval 35.0 – 50.0, which is very bad. The coefficient of determination that leadership style has a contribution of 26.3% to employee performance. The results of statistical tests (t test), obtained a value of tcount> ttable (4.218>2.013) with a significance level of (0.000 <0.05) so it can be concluded that Leadership Style contributes on Employee Performance at the East Jakarta Financial and Development Supervisory Agency